2018
DOI: 10.1515/ijeeps-2017-0232
|View full text |Cite
|
Sign up to set email alerts
|

Islanding Detection Technique based on Karl Pearson’s Coefficient of Correlation for Distribution Network with High Penetration of Distributed Generations

Abstract: This article proposes a new Karl Pearson’s coefficient of correlation (‘r’) based islanding detection scheme which utilizes negative sequence voltage and voltage unbalance signal. In order to check the legitimacy of the proposed technique, large numbers of non-islanding and islanding events are generated by modeling IEEE 34-bus network. This scheme detects islanding situation even under 0 % power mis-match condition and thus, reduces the non detection zone (NDZ). Furthermore, the proposed technique detects isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The results showed that, from the perspective of MILC, there may be certain differences in gene expression between dicotyledonous plants and monocotyledonous plants of chloroplast genomes. Karl Pearson’s correlation analysis between SCUO and MILC was used to explore the effect of CUB ( Sareen et al, 2018 ). Based on the gene expression level, we observed a significant positive between SCUO and MILC values ( P < 0.01; Table 4 ), indicating that the gene expression levels may be affected by the CUB.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that, from the perspective of MILC, there may be certain differences in gene expression between dicotyledonous plants and monocotyledonous plants of chloroplast genomes. Karl Pearson’s correlation analysis between SCUO and MILC was used to explore the effect of CUB ( Sareen et al, 2018 ). Based on the gene expression level, we observed a significant positive between SCUO and MILC values ( P < 0.01; Table 4 ), indicating that the gene expression levels may be affected by the CUB.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the reliability of the simulation of the nature and rate of change of the selected parameters, it is proposed to use one of the most common statistical methods for assessing the degree of similarity -correlation analysis, which makes it possible to determine the correlation between the change in the parameters of the power system in the case of disturbances in the ST and HRTSim. To quantify the correlation, the Pearson's correlation coefficient (r) is used [33], the absolute value of which ranges from 0 to 1. The closer r is to 1, the more similar the nature of the compared time series is.…”
Section: B Validation Criteriamentioning
confidence: 99%
“…2101 loading condition and it is normalized [23]. ANN is trained with the selected features as input.…”
Section: Figure 1 Digital Filtering Technique Of Wavelet Transform (Wt)mentioning
confidence: 99%